Asymmetric polyetherimide membranes (PEI) for nanofiltration treatment. (August 2018) - El-Gendi, Ayman; Favre, Eric; Roizard, Denis
Graphical abstract: Process flow sheet for asymmetric PEI membranes preparation. Highlights: Preparation of PEI Membranes via casting for NF. PEI membranes studied the separation of low concentrated organic solute. The NF rejection was linked to PEI elaboration conditions and solute properties. Abstract: The work aimed to prepare co-polyalkoxyether-imide (PEI) asymmetric membranes to appreciate high flux water selective polymeric membranes appropriate for the separation of organic molecules from aqueous mixtures by nanofiltration. These membranes were prepared under controlled experimental conditions from solvent non-solvent of N, N-dimethylformamide (DMF) – water (H2 O) solutions with the corresponding polyamic acid (PAA); after the wet phase inversion in a water bath, the PAA membranes were imidized by thermal treatment. The membrane physical properties, recorded by SEM, were used to optimize the asymmetric membrane preparation to improve the separation properties by tuning the thickness of the dense top layer. The performances of nanofiltration separations were examined in the light of the influence of sets of parameters. The flux of asymmetric PEI membranes increased with an increase of applied pressure. Additional, the permeate flux and membrane permeance for pure water is better than the aqueous organic solutions. Thus, the aqueous organic solution has an influence on decreasing the flux and membrane permeance. PEI membranes showed high rejection for hydrophilic molecules, like polyethylene glycol, with molecular weight ranging from 400 to 6000 Dalton; according to molecular weight, organic rejection of 79–100% were achieved from 500 ppm aqueous solutions of organic compounds.